Bond Issuance Integrity : An Analysis of Malpractices in the Czech Republic - Radil, Tomáš (2024)
Financial stability is an important factor in the national economy. If people do not trust potentially safe investment types such as bonds, it could have negative impacts on economies. International renowned rating companies do not rate the majority of the companies issuing bonds in the Czech market. Ministry of Finance developed a methodology called Score card 2.0. to rate smaller companies. In my thesis, I will analyze potential problematic issues. I will then apply the Ministry of finance’s methodology on individual issuance. The conducted analysis has led me to the identification of common traits among problematic bond issues. Based on practical observations from the application of the Score card rating methodology, I identified potential problems with the methodology. In the end, I created a new potential methodology for improving the bond market stability environment.